MOCCASIN: a method for correcting for known and unknown confounders in RNA splicing analysis - Barry Slaff (Nature Portfolio, 2021)
Confounding factors on gene expression analysis can be analyzed by several existing tools. Here the authors develop an algorithm called MOCCASIN to correct the effect of known and unknown confounders on RNA splicing quantification.